2007
DOI: 10.1007/s00439-007-0446-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between two sequence variations in the gene for peroxisome proliferator-activated receptor-gamma and plasma homocysteine concentration. Health in men study

Abstract: The concentration of circulating homocysteine has been associated with a variety of diseases, including myocardial infarction, stroke, venous thrombosis and cognitive decline. Genetic variation has been demonstrated to play an important role in determining plasma homocysteine, however, the genes involved are incompletely understood. Ligation of the transcription factor peroxisome proliferator-activated gamma (PPARG) has been demonstrated to lower plasma homocysteine. We examined the association of two sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…AAA was defined as maximum infrarenal aortic diameter ≥30mm. The definitions of clinical risk factors such as hypertension, dyslipidaemia, and CHD were as previously described [7]. …”
Section: Methodsmentioning
confidence: 99%
“…AAA was defined as maximum infrarenal aortic diameter ≥30mm. The definitions of clinical risk factors such as hypertension, dyslipidaemia, and CHD were as previously described [7]. …”
Section: Methodsmentioning
confidence: 99%
“…The Health in Men Study is a study of men aged ≥65 years who originally participated in a population‐based randomized controlled trial of screening for AAA. Details of the design of these studies, including definitions of clinical risk factors, have been reported previously 15–17 …”
Section: Methodsmentioning
confidence: 99%
“…For example, sequence variation of methylenetetrahydrofolate reductase (MTHFR) gene has been shown to influence circulating homocysteine level [83], and sequence variation of amino acid 222 from alanine to valine (p.A222V) has been reported to elevate circulating concentrations of homocysteine [84]. The PPAR γ produces a number of isoforms which control a variety of pathways including lipid metabolism, insulin sensitivity, and inflammation [85].…”
Section: Homocysteine Protein Modification and Hypertension: Thementioning
confidence: 99%